Hypertrophic Cardiomyopathy in Athletes: A Paradigm Shift in Exercise Safety, the Role of Comorbid Factors, and the Impact of Anabolic Steroids - A Literature Review - Jakubowska, Martyna; Jakubowska, Paulina; Szaryński, Mikołaj; Gólcz, Julia; Sikorski, Adam; Gólcz, Adrian; Kadłubowska, Karolina; Rytel, Jan; Chojnowska, Natalia; Bursztyn, Tomasz; Bursztyn, Michał (Quality in Sport, 2026)
Hypertrophic cardiomyopathy (HCM) in athletes is a complex condition requiring individualized risk assessment and interdisciplinary management. Advances in diagnostics, including advanced cardiac imaging and multiparametric risk stratification, allow differentiation between pathological hypertrophy and physiological adaptations in athletes. Current guidelines support carefully supervised participation in moderate and, in selected cases, high-intensity physical activity for low-risk patients. Targeted therapy, particularly the myosin inhibitor mavacamten, improves left ventricular outflow gradients, exercise tolerance, and quality of life, especially when combined with personalized training programs. Chronic use of anabolic-androgenic steroids can induce HCM-like cardiomyopathy, promote fibrosis, impair diastolic function, and increase arrhythmic risk, highlighting the need for thorough history-taking and advanced imaging. Comorbidities such as hypertension, obesity, and coronary artery disease exacerbate remodeling and arrhythmic risk, while complications like atrial fibrillation, HFpEF, and sudden cardiac death remain critical considerations. An integrated approach combining diagnostics, therapy, exercise guidance, and management of comorbidities allows safer and more flexible physical activity for athletes with HCM.